Reverse frontal lifting: alternative for the treatment of pachydermoperiostosis - Ronaldo Pontes; Amanda Figueira Bussade; Márcia De Queiroz Araújo Gomes; Luis Alejandro Vargas Guerrero; Gisela Hobson Pontes (Revista Brasileira de Cirurgia Plástica)
Introduction: Patient diagnosed with pachydermoperiostosis, presenting a strong cutaneous manifestation, making it impossible to correct the defect by the usual facial lifting techniques. The reverse frontal facelift was the idealized technique for this case. It is an innovative technique, there being no previous publication in the literature. Case report: Italian male patient, 56 years old, with cutaneous manifestation syndrome, especially in the frontal region of the face, with leathery inelastic skin, which generated aesthetic discomfort, predisposing for a syndromic stigma. Methods: The technique developed for this case involves an incision, which starts at the root of the helix (point A), bypasses the eyebrow in a sinuous line distant half a centimeter from the implantation of the eyebrow hair, going to the glabella, curving towards the nasal root and going to meet identical dimensions on the other side. From point A, a curved line also leans towards the medial direction, at a distance of 2 cm. The intention is to reduce the distance between the area to be pulled and the incision area, in order to obtain more traction, thus enabling the correction of the aspect of the face in focus. Results: Caudal traction of the flap by a supraciliary incision made it possible to correct the defect in the frontal region without altering the capillary implantation line or causing excessive eyebrow rise. Conclusion: The reverse frontal lifting technique was created for a specific case of pachydermoperiostosis syndrome. When correctly indicated, this technique can be used to achieve good results.